SINTESIS SELULOSA DARI LIMBAH AMPAS TEBU (Saccharum Officinarum L.) DENGAN METODE HIDROLISIS ASAM DAN ULTRASONIKASI - Balqis Saniatul Mukarromah; Dina Kartika Maharani (Unesa Journal of Chemistry, 2025)
The annual increase in sugar factory production can lead to a yearly rise in bagasse waste. An alternative to minimize the increase in bagasse waste is to utilize it as nanocellulose. Bagasse contains 52.7% cellulose, 20% hemicellulose, and 24.2% lignin. The synthesis of nanocellulose was carried out using a combination of chemical and mechanical methods, namely acid hydrolysis and ultrasonication, resulting in a final yield of 39.96%. The FTIR spectra of raw bagasse and bagasse-derived nanocellulose showed changes indicating that the synthesis successfully removed non-cellulosic components such as lignin and hemicellulose. After the nanocellulose synthesis process, a small shoulder appeared at a 2θ angle of 14.5˚, indicating that the synthesis had successfully removed most of the amorphous structures such as lignin and hemicellulose. The nanocellulose from bagasse exhibited two diffraction peaks at 2θ angles of 16.2˚ and 22.2˚, which are characteristic of type I cellulose.